An EFL Teacher Using Gestures to Teach English at a Vocational High School in Indonesia - Maisyarah, Dikta; Maharsi , Ista (International Journal of Research in Education, 2025)
This study addresses a research gap, as there is limited research specifically exploring the use of gestures in vocational high schools in Indonesia settings, even though Vocational High schools have distinct needs, learning styles, and challenges compared to those in general education. Moreover, real classroom practices of EFL teachers using gestures remain under-documented, despite their importance for teacher development and training.  Gestures play crucial roles in language learning, particularly in EFL contexts where students' proficiency in understanding classroom instructions varies. The subject of the research is a 43-year-old vocational high school English teacher. Data was collected from a video segment of 53 minutes. The research was conducted, and gestures were identified and analyzed following Sato's gesture categorization and using a qualitative research design. Findings indicate that the teacher participant employed Emblems, Deictic, Iconic, Metaphoric, Head Movement, Beats, and Affect Display. The gestures help teachers deliver the learning materials and communication messages, emphasize meanings and intention, and represent abstract objects. The implications of this study suggest the need to raise awareness and integrate gesture use into EFL teaching practices, because many teachers still have yet to use nonverbal behavior in teaching and lack the perception that gestures are vital when communicating, especially in teaching.